Individuals, citizens and collectivity in Archilochus (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
This paper examines the concepts and terms employed for individuals (proper and ethnic names), citizens (astoí, polítai), and the collectivity (dēmos, ethnic names) in the fragments of Archilochus.